Intracellular pH changes in isolated bovine articular chondrocytes during the loading and removal of cryoprotective agents. - Xu, X; Cui, Z; Wilkins, R; Urban, J (2003)
The addition and removal of a cryoprotective agent (CPA) are necessary steps in the cryopreservation of natural or engineered tissue products. However, the introduction and removal of CPAs induces dramatic chemical changes inside tissues and cells and these could cause irreversible damage. This study examined the effect of CPA loading and removal on the intracellular pH of isolated bovine articular chondrocytes using a fluorimetric technique. Chondrocytes that had been isolated from bovine articular cartilage were loaded with the pH-sensitive fluorophore 2('),7(')-bis(carboxyethyl)-5(6)-carboxyfluorescein. After removal of the extracellular fluorophore, the intensity of fluorescence was used to measure the intracellular pH according to a pre-determined calibration curve. Changes of intracellular pH in chondrocytes were measured following their exposure to dimethyl sulfoxide (Me(2)SO) and glycerol at concentrations of 0.6, 0.9, and 1.2M and later to the isotonic or hypertonic solutions that were used to remove the CPA. The effect of the presence of NaCl on the intracellular pH during CPA removal was also examined. The temperature was maintained at 37 degrees C. Trypan blue exclusion was used to quantify cell membrane integrity after the addition and removal of CPA. It was found that when the cells were exposed to CPA, the intracellular pH decreased quickly and recovered gradually later. During CPA removal, the intracellular pH rose following exposure to isotonic Hepes-buffered medium, but the opposite was observed if the Hepes buffer solution contained no NaCl; this was ascribed to the role of NaCl in cell membrane transport. It was noted that the change in intracellular pH correlated with the cell volume excursion, which could be estimated by the Kedem-Katchalsky model, and was linked to cell survival. The resulting alteration of pH inside the cells might contribute to cell damage and loss of function after cryopreservation.